Intelconn Smart Connection System to Improve Battery Energy Storage Reliability - Rahman, Sutisna Abdul; Fathurozzi, Raedy (Internet of Things and Artificial Intelligence Journal, 2025)
Degradation in battery cells is an unavoidable phenomenon, especially in battery modules connected in parallel. Inconsistencies in current distribution and temperature rise can accelerate degradation and pose potential safety issues. Therefore, evaluation and mitigation strategies are needed to reduce the impact of degradation on each battery cell. This research develops an extended single-particle model with Pade's approach and Taylor expansion to simplify the conventional electrochemical mechanism. Based on this approach, a multidomain electrochemical mechanism simulation model for battery modules connected in parallel is developed. The model was used to analyze the effect of cell degradation on battery module voltage, internal current distribution, and temperature rise under various charging and discharging conditions. The evaluation was conducted using the parameter sensitivity analysis method to assess the contribution of each parameter to the degradation of the parallel-connected battery cells. The results of this study are expected to help in identifying battery cells that degrade faster and developing optimal strategies in battery management for longer life and safe use.